1977
DOI: 10.1111/j.1432-1033.1977.tb11431.x
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Protein A from a Methicillin‐Resistant Strain of Staphylococcus aureus

Abstract: Protein A has been isolated from a methicillin‐resistant strain of Staphylococcus aureus, A676, which produces only extracellular protein A. The material is homogeneous after a one‐step separation and has a molecular weight of 41000. Its physicochemical and immunochemical properties have been studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0

Year Published

1977
1977
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(17 citation statements)
references
References 31 publications
2
15
0
Order By: Relevance
“…This means that S. aureus has at least two proteins recognizing vWf, one cell-surface-attached and one secreted as reported in this paper. To further complicate the picture, it has been reported that protein A in some strains exists in a soluble form, not bound to the surface of S. aureus (Lindmark et al, 1977). The function and importance of vWpb during S. aureus infections is not yet known.…”
Section: Possible Consequences Of the Interaction Between S Aureus Amentioning
confidence: 99%
“…This means that S. aureus has at least two proteins recognizing vWf, one cell-surface-attached and one secreted as reported in this paper. To further complicate the picture, it has been reported that protein A in some strains exists in a soluble form, not bound to the surface of S. aureus (Lindmark et al, 1977). The function and importance of vWpb during S. aureus infections is not yet known.…”
Section: Possible Consequences Of the Interaction Between S Aureus Amentioning
confidence: 99%
“…However, a small portion of SPA can be released into the extracellular environment during exponential growth in vitro (45)(46)(47). Some strains of MRSA produce only extracellular protein A (48). The release mechanism is unknown and the significance has not been previously evaluated in vivo.…”
Section: Chemokinementioning
confidence: 99%
“…This should be reflected by the presence of a C-terminal structure in region C not homologous to corresponding subregions in regions D, A, and B, which, however is not the case. The problem may be solved by sequence analysis of proteinA from bacterial mutants which do not exhibit blocked N-termini [29,30].…”
Section: The Proposed Primary Structure Of the Total Fc-binding Portimentioning
confidence: 99%